2008
DOI: 10.1002/ajmg.b.30692
|View full text |Cite
|
Sign up to set email alerts
|

No association between the protein tyrosine phosphatase, receptor‐type, Z Polypeptide 1 (PTPRZ1) gene and schizophrenia in the Japanese population

Abstract: NRG1-ERBB signaling influences the risk for schizophrenia pathology. A recent study has reported that MAGI1, MAGI2, and protein tyrosine phosphatase, receptor-type, Z polypeptide 1 (PTPRZ1; located on 7q31.3) gene products regulate the NRG1-ERBB4 signaling pathway, and PTPRZ1 is associated with schizophrenia in a Caucasian population. By applying a gene-based association concept, we analyzed any association between PTPRZ1 tagging SNPs and schizophrenia in the Japanese population (576 schizophrenics and 768 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…RPTPβ is expressed in oligodendrocytes, and appears to modulate ERBB4 signaling. Association analysis of PTPRZ1 showed highly significant association of this gene to schizophrenia in this first study, however, this association was not replicated in a Japanese cohort (Ito et al, 2008). …”
Section: Geneticsmentioning
confidence: 58%
“…RPTPβ is expressed in oligodendrocytes, and appears to modulate ERBB4 signaling. Association analysis of PTPRZ1 showed highly significant association of this gene to schizophrenia in this first study, however, this association was not replicated in a Japanese cohort (Ito et al, 2008). …”
Section: Geneticsmentioning
confidence: 58%
“…Recent studies suggested that proteoglycans regulate Neuregulin/ErbB signaling, and thus are related to psychiatric disorders. Buxbaum et al ( 2008 ) reported that PTPRZ1 , which encodes both PTPζ and phosphacan, is associated with schizophrenia in a Caucasian population, although no association was found in the Japanese population (Ito et al, 2008 ). They demonstrated that PTPζ binds with ErbB4 through the scaffolding protein, MAGI, and inhibits the Neuregulin-1/ErbB4 signaling.…”
Section: Proteoglycans Psychiatric Disorders and Intellectual Disabmentioning
confidence: 99%
“…FGD4 is widely involved in the myelination of the vertebrate nervous system, and its deficiency can trigger the demyelination of the peripheral nerves in patients [ 47 , 48 ]. As a protein tyrosine phosphatase, PTPRZ1 is seen as a potential susceptibility gene for schizophrenia [ 49 , 50 , 51 ]. Study reports suggest that NEBL is associated with small and medium-sized vasculitis in Kawasaki disease, which, combined with GO analysis, suggests a possible association with neuronal projection and recognition [ 52 ].…”
Section: Discussionmentioning
confidence: 99%